Educational Strategies to Enhance Motor and Language Development in Children with Stunting: A Systematic Review - Rahmadaniah, Indah; Wisuda, Aris Citra; Sansuwito, Tukimin bin (International Journal Scientific and Professional, 2025)
Stunting in early childhood is a complex health problem with broad impacts, not only on physical growth but also on motor and language development, which are essential for children's future success. This review was conducted to identify and synthesize the latest scientific evidence on the effectiveness of various educational approaches in stimulating motor and language development in children with stunting. A systematic literature search was carried out through nine scientific databases, covering publications from 2014 to 2024. Articles that met the inclusion criteria were assessed for quality using the JBI appraisal tool and analyzed thematically. A total of 23 primary articles were analyzed, showing that family- and community-based educational interventions—such as home visits, educational games, simple stimulation media, and the Montessori approach—had a positive impact on improving fine motor, gross motor, and both expressive and receptive language skills in stunted children. Approaches that involved active parental participation and were tailored to the local context proved to be more effective than general or non-targeted methods. This review emphasizes the need to strengthen education-based early stimulation programs in Indonesia’s national strategy for addressing stunting.